Inuit children and crew members bringing ice to whaling schooner A.T. Gifford, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1907)
View of Inuit children and crew members of the whaling schooner A.T. Gifford bringing ice to the vessel, Hudson Bay, ca. 1907-1909. The ice is apparently being transported on sleds. The A.T. Gifford can be seen to the right. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo 183. The ice was melted during the winter to provide water for cooking and washing. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.